O silêncio de Deus segundo Hans Urs von Balthasar - Ribaric, Sergio Alejandro (2011)
Many questions come to us from the tragedies and atrocities that mark the history. Mankind has faced so many situations that put the speech about God in shock. The analysis of the history of man leads to the impossibility of speaking of God from traditional ideas of a transcendent God, unchanging, omnipotent. Cans someone speak of a God active in the world, before the pain, the misery and human tragedy? If He can talk to us and modify a situation of pain and He does not do, so Is God a malicious or negligent. And if He can not, Can we still define him as an omnipotent God? How Cans the theology answer the question about to behold God in a world capable of such atrocities as Auschwitz and Hiroshima? Would not the theology need to search for new paradigms that may speak of God from the man's scream? The pain experienced by Jesus, would not be a way to reflection. The present work in the Theology of Hans Urs von Balthasar, brings the elements of the question for this study of God's silence. In his mystical bias, and about studies of Kenosis of the three persons of the Trinity seeking to find the way, opening up about two connotations of silence: The silence of God and a silence of God front to human suffering. It can not talk of God's silence without seeking the elements within the mystical understanding and dimension trinitarian of God revealed in the cross of Christ. The reflections contained here seek some responses in the Christology of Hans Urs von Balthasar. The God that Jesus show us, it's a God of the relegation, Kenotic, the total annihilation of his divinity and that acquires the form of a servant, as opposed to God magical and majestic that is always expected by the man. The God's presence in disasters and major tragedies of humanity, has always been overlooked, unnoticed and questioned. This study aims to seek God in His own choice: to be present where the the man's pride prevents him to find God : In the man's suffering. In shame and humiliation that man imposes on others , the poor's weakness , about one that is helpless and in the foolishness of the cross of Jesus Christ